Effect of Doxycycline on Aseptic Reperfusion Injury in Ovarian Torsion - Bektas, Gizem; Karasu, Yetkin; Yurtcu, Engin; Togrul, Cihan; Özyer Sen, Sebnem; Onder Dirican, Aylin; Uzunlar, Ozlem; Gungor, Tayfun; Caydere, Muzaffer (Gynecology Obstetrics & Reproductive Medicine, 2019)
Objective: Reperfusion injury occurs when the condition causing ischemia in ovarian torsion is corrected and the blood supply is re-established. The aim of this study is to evaluate whether doxycycline treatment reduces reperfusion injury in a rat model. Study Design: Thirty-five female albino Wistar rats were split into the five groups. Sham: Sham operation; ischemia (I): 2 hours of ischemia; ischemia and reperfusion (I/R): 2 hours of ischemia followed by 2 hours of reperfusion; Sham-Dc: Sham operation and doxycycline 10-mg/kg (2 hours prior to surgery); I/R-Dc: 2-hours of ischemia and doxycycline 10-mg/kg and 2-hours of reperfusion. The groups were compared in terms of histological and biochemical features. A semi-quantitative histological assessment scoring system was used for the histological examination. Follicular cell degeneration, vascular congestion, haemorrhage and inflammatory cell count were evaluated for histological analysis. For biochemical analysis of reperfusion injury, the body’s total antioxidant status and total oxidant status were measured using a fully automatic method. The oxidative stress index was calculated by dividing total antioxidant status by total oxidant status. Results: In the sham group the ovaries were histologically normal. Oedema, vascular congestion, bleeding, leukocyte infiltration and follicle degeneration were increased in other groups (p<0.05). There was less leukocyte infiltration in the I/R-Dc group compared to I/R group. Other histological features were similar in these groups. Doxycycline increased the malondialdehyde, total antioxidant and total oxidant status levels in Sham-Dc and I/R-Dc groups. This increase was statistically significant between Sham and Sham-Dc groups. However, although there was an increase in the biochemical markers in the I/R-Dc group, this increase was not significant compared to I/R group. Conclusion: Doxycycline treatment in ovarian torsion does not reduce I/R injury. Doxycycline may even increase reperfusion injury, according to biochemical findings.